2012
DOI: 10.1016/j.ijthermalsci.2012.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer enhancement in a straight channel via a rotationally oscillating adiabatic cylinder

Abstract: Lock-in regime Time periodic flow and heat transfer a b s t r a c t Heat convection from the uniformly heated walls of a straight channel in presence of a rotationally oscillating cylinder (ROC) is simulated at Re ¼ 100. Heat transfer enhancement due to vortex shedding from the ROC is investigated. Systematic studies are performed to explore the rotation angle and frequency influences on heat transfer by varying the latter in range of the lock-in regime and the former from 0 to 2p/3. All simulation results are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 17 publications
1
22
1
Order By: Relevance
“…In case 2, the force convection heat transfer from a stationary circular cylinder inside the channel was computed. As shown in Figure 5, the time averaged Nusselt numbers were compared with those of Beskok et al [11] and demonstrated good conformity.…”
Section: Methodsmentioning
confidence: 54%
See 1 more Smart Citation
“…In case 2, the force convection heat transfer from a stationary circular cylinder inside the channel was computed. As shown in Figure 5, the time averaged Nusselt numbers were compared with those of Beskok et al [11] and demonstrated good conformity.…”
Section: Methodsmentioning
confidence: 54%
“…In accordance to their results, transversely oscillating cylinder with 75% of the natural vortex shedding frequency had the best performance. Beskok et al [11] investigated the effect of oscillation angle and frequency of circular cylinder on heat transfer enhancement in a channel with heated walls at Re=100. They found that heat transfer enhancement could be achieved by increasing oscillation angle with a frequency equal to 0.8 of the cylinder natural frequency.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Hussam, Thompson & Sheard (2012b) reported that the optimum perturbations leading to Kármán vortex shedding are localized in the near-wake region around the cylinder, which can be excited by a cylinder oscillation. Studies have examined cylinder rotation about its own axis (Beskok et al 2012;Hussam, Thompson & Sheard 2012a), or oscillated in either a transverse direction (Yang 2003;Fu & Tong 2004;Celik, Raisee & Beskok 2010) or in line with the incident flow (Griffin & Ramberg 1976). The resulting vorticity field in all cases are similar, despite the different oscillation mechanisms (Beskok et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have examined cylinder rotation about its own axis (Beskok et al 2012;Hussam, Thompson & Sheard 2012a), or oscillated in either a transverse direction (Yang 2003;Fu & Tong 2004;Celik, Raisee & Beskok 2010) or in line with the incident flow (Griffin & Ramberg 1976). The resulting vorticity field in all cases are similar, despite the different oscillation mechanisms (Beskok et al 2012). It has been found that increasing oscillation amplitude leads to a higher convective heat transfer from a hot wall (Yang 2003;Beskok et al 2012), though the gains become more modest at larger amplitudes (Hussam et al 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…Also, by increasing the non-dimensional rotational speed of the cylinder, both the Nusselt number and the drag coefficient decrease rapidly. In our last work [19], heat transfer enhancement in a channel via a rotationally oscillating cylinder was investigated. It was found that the maximum heat transfer was achieved when the oscillating frequency is 80% of the natural frequency of vortex shedding in presence of a stationary cylinder.…”
Section: Introductionmentioning
confidence: 99%